Preoperative Factors Affecting Postoperative Early Quality of Life During the Learning Curve of Holmium Laser Enucleation of the Prostate - Kang Jun Cho; Hyo Sin Kim; Jun Sung Koh; Seung Bum Han; Sang Hoon Kim; Hyun Woo Kim; Su Yeon Cho; Joon Chul Kim (International Neurourology Journal, 2013)
Purpose: The aim of this study was to investigate the preoperative factors related to early quality of life (QoL) in patients with benign prostatic hyperplasia after holmium laser enucleation of the prostate (HoLEP) during the surgeon’s learning curve. Methods: The medical records of 82 patients with a follow-up period of at least 3 months who were treated with HoLEP during the time of a surgeon’s learning curve were analyzed retrospectively. We divided the patients into two groups on the basis of the QoL component of the International Prostate Symptom Score (IPSS) 3 months after HoLEP: the high QoL group (IPSS/QoL≤3) and the low QoL group (IPSS/QoL≥4). Preoperative factors in each group were compared, including prostate volume, prostate-specific antigen, history of acute urinary retention (AUR), urgency incontinence, IPSS, and urodynamic parameters. Detrusor underactivity was defined as a bladder contractility index less than 100 on urodynamic study. Results: A total of 61 patients (74.3%) had a high QoL, whereas 21 (25.7%) had a low QoL. A history of AUR, detrusor pressure on maximal flow (PdetQmax), bladder outlet obstruction grade, bladder contractility index, and detrusor underactivity were associated with postoperative QoL in the univariate analysis. In the multivariate analysis, a history of AUR and PdetQmax were independent factors affecting postoperative QoL. Conclusions: A history of AUR and bladder contractility affect early QoL, and preoperative urodynamic study plays an important role in the proper selection of patients during the HoLEP learning curve.